Analisis Shirkah Inan dan Samsarah Pada Homestay Syariah dengan Online Travel Agent (OTA) di Sidoarjo - Dea Silfani Robi Putri (Universitas Islam Lamongan, 2021)
Abstract: This research entitled Analysis of Shirkah Inan and Samsarah on Sharia Homestay Cooperation with Online Travel Agent (OTA) in Sidoarjo, aims to answer the questions: How to cooperate sharia homestay with online travel agent and How to form profit and obstacles in the implementation of sharia homestay cooperation with online travel agent. The research method used is a descriptive qualitative analysis approach. Data collection is done by observing, documentation, and interviews directly to the source, namely Homestay Airy Eco Sharia’s Manager and Dharmawati Homestay Sharia’s Owner. The findings show that the cooperation established between Homestay Airy Eco Sharia and Airy is a collaboration in the form of Shirkah Inan, while the cooperation established between Dharmawati Homestay Sharia and Online Travel Agent is cooperation in the form of Samsarah. From this research, it can be concluded that the cooperation conducted by Homestay Airy Eco Sharia with Airy already fits the term of cooperation in sharia economic perspective. Meanwhile, the cooperation held by Dharmawati Homestay with online travel agent is still not fulfilled the requisites of cooperation in the perspective of sharia economy. In line with above conclusions, the researcher advises that Homestay Airy Eco Sharia which conducts cooperation with Airy is expected to be sustainable. For Dharmawati Homestay Sharia who conducts cooperation with online travel agent is expected to be able to introspect each other and evaluate the cooperation systems carried out in order to remain on sharia economic principles. Keywords: cooperation; sharia homestay; online travel agent (OTA)